Prevalence of Cholera among Admitted Patients of Federal Medical Centre (FMC), Keffi, Nasarawa State, Nigeria: A Retrospective Observational Study (Lafia Journal of Scientific and Industrial Research, 2026)
This study evaluates the epidemiological trends, morbidity, and mortality patterns of cholera among patients at Federal Medical Centre (FMC) Keffi from 2021 to 2025. The findings revealed fluctuating case incidence with peaks in 2022 and resurgence in 2025, alongside a persistently high case fatality rate. Age-specific outcomes demonstrated a U-shaped mortality pattern affecting both pediatric and geriatric populations, while sex-based outcomes showed no significant difference. These findings align with national trends in Nigeria, where cholera remains endemic due to poor water, sanitation, and hygiene (WASH) conditions. The study emphasizes the need for improved surveillance, early diagnosis, and targeted interventions.
Keywords: Cholera; Epidemiology; Case Fatality Rate; Morbidity; Mortality; Public Health